2015
DOI: 10.1103/physreve.91.050801
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the puzzling intermediate states in the Biham-Middleton-Levine traffic model

Abstract: The Biham-Middleton-Levine (BML) traffic model, a cellular automaton with eastbound and northbound cars moving by turns on a square lattice, has been an underpinning model in the study of collective behavior by cars, pedestrians, and even internet packages. Contrary to initial beliefs that the model exhibits a sharp phase transition from freely flowing to fully jammed, it has been reported that it shows intermediate stable phases, where jams and freely flowing traffic coexist, but there is no clear understandi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A comparison with the square lattice. The critical density ρ c =0.244(3) for the BML model on a honeycomb is lower that the value of 0.283(2) for the lowest transition on a square lattice [28]. However, this order is reversed in at least two cases.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…A comparison with the square lattice. The critical density ρ c =0.244(3) for the BML model on a honeycomb is lower that the value of 0.283(2) for the lowest transition on a square lattice [28]. However, this order is reversed in at least two cases.…”
mentioning
confidence: 67%
“…Driven by car density, the system falls into three different phases: free flow (all vehicles move), jammed phase (all vehicles are stuck) and intermediate states where jams and free flow coexist on a wide density range [25][26][27]. A recent study have shown that such intermediate states are a consequence of the anisotropy inherent to the model [28], which produces two different phase transitions: one if the system is longer in the flow direction (longitudinal) and other if the system is longer in the perpendicular one (transversal). It has also been reported that this intermediate phase disappears when some kind of randomization is introduced [26,29,30], or the traffic periods for the two cars are increased [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This problem has attracted the interest of scientists and engineers to research the dynamic characteristics of tra±c°ow, and a lot of models have been proposed, such as°uid *Corresponding author. models, [1][2][3][4] car-following models, 5-10 cellular automata models (CA model) [11][12][13][14][15][16][17] and so on. By those models, some basic characteristics of tra±c°ow, i.e.…”
Section: Introductionmentioning
confidence: 99%